Solve for k -6k-13=83

Math
-6k-13=83
Move all terms not containing k to the right side of the equation.
Tap for more steps…
Add 13 to both sides of the equation.
-6k=83+13
Add 83 and 13.
-6k=96
-6k=96
Divide each term by -6 and simplify.
Tap for more steps…
Divide each term in -6k=96 by -6.
-6k-6=96-6
Cancel the common factor of -6.
Tap for more steps…
Cancel the common factor.
-6k-6=96-6
Divide k by 1.
k=96-6
k=96-6
Divide 96 by -6.
k=-16
k=-16
Solve for k -6k-13=83

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top